Sagehood : the contemporary significance of neo-Confucian philosophy - Angle, Stephen C., 1964- (New York ; Oxford : Oxford University Press, 2009)
Angle's book is both an exposition of Neo-Confucian philosophy and a sustained dialogue with many leading Western thinkers especially with those philosophers leading the current renewal of interest in virtue ethics. He argues for a new stage in the development of contemporary Confucian philosophy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Neo-Confucianism.